= 1*2*3*4*5*6*7*8*(9-1-8)
=1*2*3*4*5*6*7*8*0
=0
\(A=1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9-1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8-1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot8\)
\(=1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9-1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot1-1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot8\)
\(=1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot\left(9-1-8\right)\)
\(=1\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot0=0\)
A=1.2.3.4.5.6.7.8.9 - 1.2.3.4.5.6.7.8 - 1.2.3.4.5.6.7.8.8
A=(1.2.3.4.5.6.7.8).9 - (1.2.3.4.5.6.7.8).1 - (1.2.3.4.5.6.7.8).8
A=(1.2.3.4.5.6.7.8).(9-1-8)
A=(1.2.3.4.5.6.7.8).0 = 0
A=1.2.3.4.5.6.7.8.9 - 1.2.3.4.5.6.7.8 - 1.2.3.4.5.6.7.8.8
=(1.2.3.4.5.6.7.8).9 - (1.2.3.4.5.6.7.8).1 - (1.2.3.4.5.6.7.8).8
=(1.2.3.4.5.6.7.8).(9-1-8)
=(1.2.3.4.5.6.7.8).0
= 0